Economic evaluation of a community-based diagnostic pathway to stratify adults for non-alcoholic fatty liver disease: a Markov model informed by a feasibility study - Tanajewski, Lukasz; Harris, Rebecca; Harman, David J.; Aithal, Guruprasad P.; Card, Timothy R.; Gkountouras, Georgios; Berdunov, Vladislav; Guha, Indra Neil; Elliott, Rachel (BMJ Publishing Group Ltd, 2017)
Objectives: To assess the long-term cost-effectiveness of a risk stratification pathway, compared with standard care, for detecting non-alcoholic fatty liver disease (NAFLD) in primary care.